Comparing candidates' beliefs and exam performance in speaking tests - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Cristina Pérez-Guillot Julia Zabala-Delgado Universitat Politècnica de València, Spain   ABSTRACT The development of a language exam is not a linear process but rather a round cycle in which, by using the test, we obtain information that will in turn be applied to improve each of the steps in the cycle. The goal of our study was to analyse students' beliefs about their performance in the speaking section of a language proficiency exam and compare them with their actual results in the exam, in order to determine whether their beliefs were based on their actual level of competence or if they were based on other factors, such as anxiety or stress due to the particular characteristics of this section of the exam.